2002
DOI: 10.1002/gps.606
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and the nigrostriatal dopaminergic system

Abstract: The identification of strategies to improve dopaminergic transmission may delay the onset of motor and cognitive deficits associated with normal ageing. In order to develop effective preventative strategies, the causative mechanisms underlying age-related changes and the interaction between synaptic structure and function need to be more clearly elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 126 publications
1
82
1
4
Order By: Relevance
“…While we covaried for age in all our analyses, we also explicitly tested for age-related effects given the extensive literature documenting age-related alterations in DA neurotransmission. 41 We found neither a main effect of age (F(21,88) = 0.948, P = 0.534) nor any age  genotype interactions (all P-values > 0.1) on reward-related VS reactivity. Moreover, all patterns of genotype-modulated reward-related VS reactivity were similar when the analyses were restricted to subjects 45 years and younger (N = 44) or subjects 46 years and older (N = 45).…”
Section: Allele and Genotype Frequenciescontrasting
confidence: 56%
“…While we covaried for age in all our analyses, we also explicitly tested for age-related effects given the extensive literature documenting age-related alterations in DA neurotransmission. 41 We found neither a main effect of age (F(21,88) = 0.948, P = 0.534) nor any age  genotype interactions (all P-values > 0.1) on reward-related VS reactivity. Moreover, all patterns of genotype-modulated reward-related VS reactivity were similar when the analyses were restricted to subjects 45 years and younger (N = 44) or subjects 46 years and older (N = 45).…”
Section: Allele and Genotype Frequenciescontrasting
confidence: 56%
“…Combined declines in cognitive and motor processes with age could be due to declining dopaminergic function. Indeed, the nigrostriatal dopaminergic system plays a major role in the control of both cognitive and motor processes (Nieoullon and Coquerel 2003), and its deterioration with aging has been implicated in an array of cognitive (Arnsten and Goldman-Rakic 1985;Arnsten et al 1994;Moore et al 2005;Reeves 2005;Reeves et al 2002) and motor deficits (Emborg and Kordower 2002;Grondin et al 2000;Irwin et al 1994). Volkow et al (1998) provided support for this hypothesis, by showing that D2 receptor availability in the caudate and putamen in healthy elderly subjects was positively correlated with performance on a finger tapping task and performance on specific cognitive tasks dependent on frontal function.…”
Section: Introductionmentioning
confidence: 99%
“…As to the latter, although most studies have found a negative linear relationship between adult age and DA (see Reeves et al, 2002, for a review), some research indicates a curvilinear trajectory, with accelerated losses from young-old to very-old age (Rinne et al, 1990;Antonini et al, 1993;Bannon and Whitty, 1997;Ma et al, 1999).…”
mentioning
confidence: 99%